The Charismatic Leadership of Quaid-i-Azam Muhammad Ali Jinnah: His Vision and Constitutionalism - Shabbir, Ghulam; Jawad, Khizar; Hanif, Kalsoom (Pakistan Languages and Humanities Review, 2022)
This study aims to critically evaluate the charismatic leadership of Quaid-i-Azam Muhammad Ali Jinnah. Moreover, to examine his vision and constitutional approach towards the issues of the Muslims. Through an extensive review of the literature, primary and secondary sources have been consulted. This paper provides an in-depth analysis of the various aspects of Jinnah’s charismatic leadership. Mainly this study provides insight to understand his vision to solve the issues of his community through a constitutional approach. These constitutional means provided him with a comprehensive direction to negotiate the issues with British authorities and the All-India National Congress. The findings of this study reveal that his methods and approaches help a reader to understand the situational factor and task management of Jinnah, which rightly ascertained him as a charismatic leader. Max Weber’s theory of charisma is utilized to evaluate the political leadership of Jinnah. In this research historical, descriptive and analytical methods have been utilized.